The relationship between individualism-collectivism and conflict resolution styles: a cross cultural study between Schlumberger Financial Center (M) & Honda Manufacturing (M) / Muhamad Shukri Abdul Razak and Mohd Hafiz Mohd Razali - Abdul Razak, Muhamad Shukri; Mohd Razali, Mohd Hafiz (Faculty of Business and Management, 2013)
This research paper is about on how to measure the conflict resolution style among Schlumberger Malaysia Sdn Bhd and Honda Malaysia Sdn Bhd. With 2 independent variables that already identified individualism and collectivism and the dependent variable conflict resolution style the investigation on the research title have been held. 40 sets each of questionnaires had been distributed among Schlumberger and Honda employees and finding already being analyzed and interpreted where some group of respondent have their own conflict resolution style. Hence, this research aim that the Conflict resolution Style measured through the two independent variables which is Individualism , collectivism and also dependent variable which is conflict resolution style. Based on the result findings all the variables will influence a certain conflict resolution style and based on finding. The objectives of this research is to measure the relationship between individualism and conflict resolution styles in Schlumberger and Honda employees/Management, to know if Schlumberger employees type of conflict resolution style can enhance individualism, to find whether collectivism will effect which type of conflict resolution style, either the result is integrating, compromising, obliging, dominating, or avoiding. All of the objectives have been conclude that all of it is achieved and answered the research questions.